1992
DOI: 10.1136/pgmj.68.797.229
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma presenting with Addison's disease

Abstract: The commonest cause of primary adrenal failure and shrunken adrenals is autoimmune adrenalitis. The same clinical picture with adrenal masses is nowadays most commonly due to carcinomatous spread. Our case emphasizes the importance of obtaining tissue from patients such as these, where no primary lesion is apparent, as occasionally a treatable lymphoma will be found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Primary malignant lymphoma of the adrenal gland is extremely rare and so far only 30 cases have been reported in the Western countries including France [3,[26][27][28][29], Germany [30], Italy [24,31], The Netherlands [23], Spain [13,17,18,20,25], United Kingdom [10,11,19], and the United States [4][5][6][7][8][9]12,[14][15][16]21,22]. There is one reported case from Taiwan [32], another from Hong Kong [33], and 33 other cases [34][35][36][37][38][39][40][41][42][43][44][45] from Japan over the past 49 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Primary malignant lymphoma of the adrenal gland is extremely rare and so far only 30 cases have been reported in the Western countries including France [3,[26][27][28][29], Germany [30], Italy [24,31], The Netherlands [23], Spain [13,17,18,20,25], United Kingdom [10,11,19], and the United States [4][5][6][7][8][9]12,[14][15][16]21,22]. There is one reported case from Taiwan [32], another from Hong Kong [33], and 33 other cases [34][35][36][37][38][39][40][41][42][43][44][45] from Japan over the past 49 years.…”
Section: Discussionmentioning
confidence: 99%
“…The pertinent clinicopathologic features of the previously reported 55 cases, which include those in the English literature as well as those non-English reports containing enough information in the English abstracts, are summarized in Table I [3][4][5][6][7][8][9][10][11][12][13][14][15][16][18][19][20][21][22][23]28,30,[32][33][34][35]37,39,[41][42][43][44][45]. A more detailed account of each of the 30 isolated cases reported in the English literature is illustrated in Table II.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some investigators suggested that surgical debulking with subsequent chemotherapy for large masses could provide a better complete response rate [13]. Alternatively, radiotherapy could be given to a bulky mass lesion in order to prevent local recurrence [12,21]. Our patient was treated with a less intensive chemotherapeutic regimen of cyclophosphamide, vincristine, and oral prednisolone because she had a very poor performance status.…”
Section: Discussionmentioning
confidence: 97%